Troska o trzeźwość młodzieży na łamach „Młodego Hufca” w latach 1927–1939 - Biskupski, Jacek (Biuletyn Historii Wychowania, 2016)
Alcoholism among young people was a serious social issue in the years 1918-1939 in Poland. The purpose of this article is to show how in the journal “MłodyHufiec”, Poles fought alcohol consumption by young people. The article presents the actions taken to tackle alcoholism as well as to promoteabstinence among young peoplewhich appeared in the magazine in years 1927 1939.